P-635 The impact of force-degraded variants of recombinant human follicle stimulating hormone alfa (r-hFSH alfa) on in-vitro and in-vivo biological activity. (30th June 2022) - Nevelli, F; Peroglio, F; Gleixner, R; Dadone, A; Palmese, A; Lispi, M; D'Hooghe, T; D'Acunto, C.W
Abstract: Study question: Can an in-vitro bioassay assess the potency of r-hFSH-alfa force-degraded variants with similar ability to the in-vivo rat bioassay described in EU Pharmacopoeia (EU-Pharm 2285) ? Summary answer: The in-vitro bioassay showed similar ability to the in-vivo bioassay for estimating the impact of r-hFSH-alfa variants, resulting from process-related modifications, on biological activity. What is known already: The active ingredient of Gonal f ® (Merck KGaA), follitropin-alfa (INN, r-hFSH-alfa), mimics the action of endogenous FSH by binding to, and subsequently activating, the hFSH-receptor (FSH-R), regulating cellular metabolism and oocyte survival/maturation. Structural modifications in r-hFSH-alfa glycosylation, oxidation, or other biochemical changes, may occur during the r-hFSH-alfa manufacturing process and may impact its efficacy/safety. The rat in-vivo bioassay (EU Pharmacopeia) is routinely used to assess r-hFSH-alfa potency by measuring ovarian weight increase. We evaluated whether an in - vitro bioassay has the same ability as the rat in - vivo bioassay to detect changes in biological activity caused by r-hFSH-alfa structural modifications. Study design, size, duration: Three r-hFSH-alfa (Gonal f ® ) batches were stressed under eight chemical/physical/enzymatic treatments. The resulting degraded samples were compared with untreated samples using in-vivo and in-vitro bioassays. Participants/materials, setting, methods: Force-degraded r-hFSH-alfa variants were produced by chromatographic separation (acidic/basic enrichment), chemical/physical stress (acidic/basic pH incubation, thermal/oxidative stress) and enzymatic treatments (de-galactosylation and de-sialylation). r-hFSH-alfa potency was measured via a rat in-vivo bioassay ( European Pharmacopoeia 2285), assessing ovarian weight increase,  and an in-vitro bioassay (cell line expressing the transmembrane hFSH-R), assessing cell-specific metabolic cascade. Force-degraded and untreated samples were compared via analysis of variance. Main results and the role of chance: All force-degraded samples were characterized by the chemical/physical analyses panel for quality control. r-hFSH-alfa forced degradation modified the critical quality attributes of the samples; namely, increased the presence of r-hFSH-alfa oxidized forms and/or free subunits up to 50% above product specification, and modified the sialic acid level across variants, generating significantly more hypo-sialylated forms when compared with the untreated control samples. The increase in r-hFSH-alfa free subunits significantly reduced r-h-FSH-alfa biological activity compared with untreated samples, in both the in-vivo and in-vitro assays ( p  < 0.001 for both). The increase in r-hFSH-alfa oxidized forms significantly reduced r-hFSH-alfa biological activity in-vitro ( p  <0.001) and, to a lesser extent, in-vivo ( p  <0.006). A gradual decrease in r-hFSH-alfa sialylation decreased r-hFSH-alfa biological activity in - vivo, indicating a second-order polynomial correlation, and increased r-hFSH-alfa biological activity in-vitro, indicating a negative linear correlation (slope significance p <0.001, R 2 =0.996). De-sialylation reduces r-hFSH-alfa steric hindrance during the interaction of r-hFSH-alfa and the FSH-R, increasing both r-hFSH-alfa–FSH-R affinity and r-hFSH-alfa biological activity in - vitro, while increasing the rate of r-hFSH-alfa metabolism, resulting in decreased r-hFSH-alfa biological activity in - vivo . Both assays showed a similar ability to identify differences in critical quality attribute levels (sialylation, oxidation, free-subunits), with the intent to identify out-of-specification batches. Limitations, reasons for caution: r-hFSH-alfa forced degradation produced more than one structural/chemical modification in most variants (except for de-sialylation); therefore, the effect of discrete modifications could not be studied. Additional studies are needed to show that in - vitro methods can ultimately replace in - vivo bioassays to identify differences in critical quality attribute levels during r-hFSH-alfa manufacturing. Wider implications of the findings: Chemical and/or structural modifications of r-hFSH-alfa strongly impact r-hFSH-alfa biological activity and related potency. The development of an in - vitro bioassay for the accurate measurement of r-hFSH-alfa potency may serve to replace the in - vivo bioassay, according to EMA indications (CPMP/SWP728/95). Trial registration number: not applicable